The Implications of Public Relation on Customer Retention Among Nigerian Banks (Content Analysis) - Oki Isiya Torutein (IIARD International Journal of Banking and Finance Research, 2026)
The Nigerian Banking industry play vital role in the wheel of economic development of Nigeria. The role of banking industry plays such role to the economy, the shareholders and the staff. Any nation that does not have strong financial system is bound to collapse. Banks on their own need to retain their customers and also set new ones. This will enable them to have many customers which transforms to more fund and all things being equal, more money to lend to customers and more interest paid hence more profit to the banks. The Nigerian money deposit banks have devised various strategies to retain their customers like rendering home services, internet banking, and customer alert not wasting customer’s time as it was in the era of tally banking, which was characterized by long queues. Customer retention is therefore giving customers more than what they expect. These services have been exhibited by banks in various ways. This work therefore want to find out the implications of public relations on customer retention and it was found that people prefer going to these banks that they are treated like kings that they do not waste time before collecting etc. the implication is that banks today are facing stiff competition and any of them that do not engage in effective public relations are losing their customers instead of getting new ones to add to what they have. Conclusion was made that good public relations is a good strategy for customer retention. Recommendations were made that banks should adopt their own best approach to retain customers at this era of stiff competition among banks so that they don’t go distress.